Pequeña subestación de distribución que brinde a la universidad una herramienta para sus prácticas educativas. - Guerrero Alemán, Publio Andrés; Caballero Barragán, Cristian Yesid (Universidad Antonio Nariño, 2021)
This project is focused and executed for the fulfillment as a general objective of the design of the general content of a basic substation, with its respective transformer and components, this project will allow university students to have a tool for their educational practices. The characteristics of this project are based on and supported by the design and theoretical bases of the substation, to then have its execution and operation.